PENGEMBANGAN MEDIA PETA HARTA KARUN: MENGENALKAN LAMBANG BILANGAN DAN HURUF PADA KELOMPOK B DI RAM NU 251 AL-FATTAH GRESIK - Nina Nuriyah Ma'arif; Lilis Nor Dayani; Riyadlotus Sholichah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
In early childhood education (PAUD), teachers are required to carry out the learning process in a clear, interesting, fun, and educational manner. This can be done by using interesting and representative instructional media. This research focuses on the development of instructional media in order to introduce numbers and letters for pupils of Group B at RAM NU 251 Al-Fattah Gresik through the development of media